ISLAMIC LEARNING METHOD ON FILM I NOT STUPID TOO 2 - Ali Imarn Sinaga; Agus Yusuf Rajagukguk (Universitas Dharmawangsa, 2020)
The study aims to analyse and classify the Islamic learning methods contained in the film I Not Stupid Too 2. The results of this research are expected to give a thought donation about the delivery of Islamic education methods both at home and in the school environment for children and adolescents as well as a reflection material for parents and educators. This research is a research study library, and includes qualitative descriptive research that seeks to reveal a problem or event as it is. Data collection is done using the documentation method. This research uses content anaysis (content analysis) or document analysis, which means giving meaning to the data that is successfully collected and from that meaning is drawn conclusions. The results showed that the film I Not Stupid Too 2 contains many values of Islamic religious education, especially in terms of methods of learning used, so that the film is safe to consume the general public and highly recommended for educators. The result of this research is the Islamic learning methods found in the film I Not Stupid Too 2 include; Method of Mau'idzah (advice), al Targheeb method (gift giving), Tarheeb method (penalty given), amtsal Method (Parable), method of precision, exercise method, and question and answer method.